Perlakuan Coating dengan menggunakan Isolat Methylobacterium spp. dan Tepung Curcuma untuk Meningkatkan Daya Simpan Benih Padi Hibrida - Eny Widajati; Selly Salma; Yuyuk Agung Lastiandika (Buletin Agrohorti, 2013)
This research aims to study the effect of coating on seed storability in three varieties of hybrid rice. The research conducted at Centre for Soil Research, East West Corporation in Purwakarta and Laboratory of Seed Science of Department Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University.This experiment arranged in nested plot design in which formulation of seed coating (uncoated seed, TDJ-7, TD-TPB3, TD-TM1 and Curcuma flour) was nested in six times period of storage. The result showed that coated and uncoated seed still had high viability after storage 15 weeks for 3 varieties of hybrid rice seeds (DG-1 SHS, SL-8 SHS and INTNANI-2). Methylobacteriumspp. strain TD-TPB3 and TD-TM1 showed to be the best coated for hybrid rice seeds.Keyword :Curcuma, Methylobacteriumspp., storage, viability.